Quantity-Intensity Relation of Potassium in Soils of Selected Land-uses in the Humid Rainforest Agroecology, Southeastern, Nigeria - B.U. Uzoho; P.I. Owoh; I.F. Irokwe; E.U. Ekwugha; R.E. Ubakwe; J.A.L. Effiong (Bulgarian Journal of Soil Science, 2023)
Application of Q/I concept constitutes a viable approach for the estimation of soil K status and crop K requirements. Soil samples were collected from the 0-15 and 15-30 cm depths of oil palm, cassava, plantain and sycamore land-uses in the humid rainforest agroecology, Southeastern Nigeria and analyzed for K forms and Q/I parameters. Data generated for the K forms and the Q/I parameters were subjected to ANOVA and means separated using LSD at 5% probability level. Also, the K forms were correlated with soil properties and K Q/I parameters and equally amongst themselves using correlation analysis. Potassium forms significantly (LSD 0.05) decreased as total > structural > available > exchangeable > non-exchangeable > solution K. The K Q/I parameters varied significantly (LSD0.05) according to land-uses and soil depths and ranged between 1.16-2.03 Mol L-1/2 x 10-3 (ARe ok), 9.25-17.75cmol kg-1 (KL), 3.63-6.13cmol kg-1(Ko), 5.63-12.25cmol kg-1 (Kx), 6.37-9.81cmolkg-1(mol L-1) -1/2 (PBCok), 26.14-53.96 cmol kg-1(mol L-1) -1/2(Kpot), 0.82- 1.83Lmol-1) -1/2 (KG), 328.32-1562.82 KJ mol-1(-∆G) and 0.14-0.50% (Ksat). Whereas the intercorrelation of K forms was significant (P < 0.05), the correlation between K Q/I parameters with most K forms and soil properties and between K forms with most soil properties were distinct. The Q/I concept could be useful for understanding of transformation of K in soil and the prediction of K fertilizer for sustained crop performance.